KONSUMSI BUAH KURMA MENINGKATKAN KADAR HEMOGLOBIN PADA REMAJA PUTRI - Safitri Safitri; Julaecha Julaecha (Jurnal Endurance, 2021)
The impact of anemia affects the decrease in concentration and learning achievement, in the long run it affects the quality of human resources, where young women are the future generation of the nation who will determine the next generation. Based on the results of research, dates can increase hemoglobin levels because they contain substances that the body needs for the formation of red blood cells. This study aims to determine the effectiveness of dates on the increase in hemoglobin levels in adolescent girls. This research method is Quasi Experiment one group pre post test . The sample in this research is 20 students. The sampling technique was purposive sampling. The collected data were analyzed by univariate and bivariate. The results of the normality test of the distribution of data were not normally distributed, therefore the mean used was the median analyzed using a non parametric statistical test, namely Wilcoxon Signed Rank. The analysis showed that there was an increase in hemoglobin (Hb) levels with a median score (11.15 VS 12.65, P <0.05). The conclusion of this study is that there is a therapeutic effect of dates on an increase in hemoglobin levels in adolescent